Gold nanoparticles ingested by oyster larvae are internalized by cells through an alimentary endocytic pathway. Issue 8 (14th September 2018) - Noventa, Seta; Hacker, Christian; Correia, Ana; Drago, Claudia; Galloway, Tamara
Abstract: The biological fate of nanoparticles (NPs) taken up by organisms from their environment is a crucial issue for assessing ecological hazard. Despite its importance, it has scarcely been addressed due to the technical difficulties of doing so in whole organism in vivo studies. Here, by using transmission electron microscopy and energy dispersive X-ray spectroscopy (TEM-EDS), we describe the key aspects that characterize the interaction between an aquatic organism of global ecological and economic importance, the early larval stage of the Japanese oyster ( Crassostrea gigas ), and model gold NPs dispersed in their environment. The small size of the model organism allowed for a high-throughput visualization of the subcellular distribution of NPs, providing a comprehensive and robust picture of the route of uptake, mechanism of cellular permeation, and the pathways of clearance counterbalancing bioaccumulation. We show that NPs are ingested by larvae and penetrate cells through alimentary pinocytic/phagocytic mechanisms. They undergo intracellular digestion and storage inside residual bodies, before excretion with feces or translocation to phagocytic coelomocytes of the visceral cavity for potential extrusion or further translocation. Our mechanistically-supported findings highlight the potential of oyster larvae and other organisms which feature intracellular digestion processes to be exposed to man-made NPs and thus any risks associated with their inherent toxicity.